2019
DOI: 10.1080/08998280.2019.1624097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of temporal artery temperature and bladder temperature in the postanesthesia care unit

Abstract: To verify that temporal artery (TA) temperature measured in the postanesthesia care unit (PACU) in noncardiac surgical patients is a valid reflection of core temperature, a prospective, observational, institutional review board-approved study was conducted in a large, academic tertiary care hospital. The study developed from an initial quality improvement project. A total of 276 patients who had an indwelling bladder catheter as standard of care were enrolled when a research student was available over a 6month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Asadian et al found that measurements with NCTAT and ITT were safer [20]. Again, in the post-anesthesia care unit [30,31], colorectal-gynecological [23], rehabilitation period of patients with spinal cord and brain trauma [32] or in patients undergoing major surgical intervention [11,19,31], it is stated that the results of measurements made with NCTAT and ITT are agreement and that invasive measurement method should be used as a reference [11,19,30]. In a metaanalysis of 11 studies in 1764 patients, Geijer et al emphasized that NCTAT is more reliable than ITT and may replace ITT in the future [10].…”
Section: Discussionmentioning
confidence: 99%
“…Asadian et al found that measurements with NCTAT and ITT were safer [20]. Again, in the post-anesthesia care unit [30,31], colorectal-gynecological [23], rehabilitation period of patients with spinal cord and brain trauma [32] or in patients undergoing major surgical intervention [11,19,31], it is stated that the results of measurements made with NCTAT and ITT are agreement and that invasive measurement method should be used as a reference [11,19,30]. In a metaanalysis of 11 studies in 1764 patients, Geijer et al emphasized that NCTAT is more reliable than ITT and may replace ITT in the future [10].…”
Section: Discussionmentioning
confidence: 99%